Arctic Cooperation between Russia and India in the Wake of Climate Change - D. А. Zinnatullin (Евразийская интеграция: экономика, право, политика, 2024)
Global climate change has placed the region at the centre of geopolitics, as melting Arctic sea ice transforms it from a predominantly scientific interest to a contest of national security claims, commercial interests and environmental concerns, with profound implications for both the international legal and political systems. The Arctic environment is an area of common concern requiring collective behaviour by all, including Russia and India.Aim. Examine environmental issues in the Arctic policies of Russia and India, and find common ground in Arctic cooperation on climate change.Tasks. Identify existing problems and propose recommendations to address them.Methods. To solve the problems set in the study, the author uses such methods as statistical analysis, method of document analysis, discourse analysis of speeches of political leaders of Russia and India. Results. The issues of the climate agenda of Russia and India are considered. Unlike Russia, the Indian side has problems in implementing its state policy on climate change. Sharing experience in effective financing of environmental programmes, disaster risk management and information exchange are areas of potential cooperation in the context of climate change. Despite the geopolitical changes taking place around the world, Russia-India cooperation has not been interrupted, but has remained at the same level and has great potential.Conclusions. Ensuring the environmental security of Russia and India is an integral part of the policies of the two states. As the data presented in this paper show, the states have similar interests in developing measures to prevent climate change deterioration in the Arctic region.